Agricultural education as a medium for the transmission of Western science during British rule in Malaya, 1905-1957 - Arman, E.; Mamat, M.Z.; Hasbullah, M. (Taylor & Francis, 2016)
This paper traces the transmission of Western science through the agricultural education sector during the British colonial administration of Malaya. This education system included three levels: elementary, intermediate and the school of agriculture. To understand the process by which Western science was transmitted in Malaya, Basalla’s model was adopted to clarify the vectors of Western science and the types of knowledge disseminated by these vectors, and to identify the mechanisms sustaining scientific research activities outside Europe. This paper shows that the transmission and the diffusion of Western science through education were highly centralised under the British colonial umbrella and closely associated with the agricultural economy.